Evaluasi Komunikasi Edukatif Guru PAI dan Wali Siswa di SD Kecamatan Danau Sembuluh pada Masa Pandemi Covid-19 - Rapika Nor Cayani; Muslimah Muslimah (Jurnal Syntax Transformation, 2022)
Good and effective learning will provide space and opportunities so that children can learn more actively and can explore their curiosity through communication and their abilities/potential, and this requires good guidance from parents or from teachers or educators, especially religious education teachers. Islam. Teachers as learning agents are obliged to have academic qualifications obtained through accredited universities (S1/D4) and have 4 competencies. Based on the observation that during the Covid-19 pandemic, there were many learning problems, one of which was at SDN 1 Danau Sembuluh 1, Seruyan Regency and at SDN 2 Telaga Home, Danau Sembuluh Subdistrict. There are learning problems, one of which is Islamic religious education subjects. There is a lack of communication between teachers and parents. This means that in the learning system the guardians of students do not allow their children to study at home, one of which is Islamic religious education. This is very enthusiastic because the regards of the learning system as effective learning is that it will provide space and opportunities for children to learn more effectively by providing knowledge through communication between teachers and parents. The purpose of this study was to find out how to evaluate the educative communication of Islamic religious education teachers and student guardians at the Danau Sembuluh sub-district elementary school during the covid-19 pandemic. The research method used is a mixed research method or a mix of quantitative and qualitative research. Based on the results of the study that there is a comparison of communication between Islamic religious education teachers and students' guardians at SDN 1, Danau Sembuluh sub-district, Seruyan Regency and Sdn 2 Danau Sembuluh, Seruyan Regency.